Analysing the Styles and Approaches in Oseni’s Arabic Translation of the Old Nigerian National Anthem - Lawal, Rahman; Akinkunmi Rabiu, Ridwan (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2026)
Given the profound significance of the Nigerian national anthem in representing collective identities of the Nigerian populace. This study examined the translation approaches, styles and strategies employed in Oseni’s Arabic translation of the old Nigeria National Anthem (1978-2024). This study aims to evaluate the efficacy of the translation strategies adopted by the author while considering their implication for cross cultural communication. The methodological frame work for this research is the qualitative, auto-telic and content based approach. Grounded in the field of translation studies, the research employs a comparative analysis and methodology to scrutinize linguistic nuances and culture adaptation adopted. This research employed eclectic theoretical approach which includes equivalent theory, Skopos theory, and cultural translation theory. Through a careful examination of Oseni’s translation, this research work revealed that Oseni takes into account the purpose, function, and cultural nuances of the text in the source language in translating to the target language. The author also adopts stylistics devices such as rhythm and imagery to colour his translation in the recipient language in order to aesthetically attract the attention of his target audience. This work also contributes to advancing the understanding of translation theories and practice particularly with the reading of national symbols and identities. In conclusion, this work shows that trans-lingual translation involves the knowledge of extra-linguistics features such as culture and context, cosmological as well as sociological features embedded in the original text and how they are infused in the target language without distorting meaning.